Pontine Norepinephrine Defects in Mecp2-null Mice Involve Deficient Expression of Dopamine β-hydroxylase but not a Loss of Catecholaminergic Neurons - Zhang, Xiaoli (2010)
Rett syndrome is a neurodevelopmental disorder caused by Mecp2 gene mutations. In RTT patients and Mecp2-null (Mecp2(−/Y)) mice, norepinephrine (NE) content drops significantly, which may play a role in breathing arrhythmia, sleep disorders and sudden death in RTT. However, the underlying mechanisms for the NE defect are not fully understood. The NE defect may result from decreased NE biosynthesis, loss of catecholaminergic neurons or both. Although deficiency in tyrosine hydroxylase (TH) has been demonstrated, it is possible that dopamine β-hydroxylase (DBH), the critical enzyme converting dopamine to NE, is also affected. To test these possibilities, we studied DBH expressions at mRNA and protein levels in pontine catecholaminergic neurons of Mecp2(−/Y) mice identified with breathing abnormalities. In comparison to the WT, Mecp2(−/Y) mice at 2 months of age showed ~50% decrease in the expressions of DBH and TH, at both protein and mRNA levels in the locus coeruleus (LC) region. Consistently, DBH and TH immunoreactivity was markedly decreased in LC neurons of Mecp2(−/Y) mice. No evidence was found for selective deficiency in TH- or DBH-containing neurons in Mecp2(−/Y) mice, as almost all TH-positive cells expressed DBH. By counting TH-immunoreactive cells in the LC, we found that the Mecp2(−/Y) mice lost only ~5% of the catecholaminergic neurons as compared to wild-type, although their LC volume shrank by ~15%. These results strongly suggest that the NE defect in Mecp2(−/Y) mice is likely to result from deficient expression of not only TH but also DBH without significant loss of catecholaminergic neurons in the LC.